Spontaneous postnatal growth is reduced in children with CHARGE syndrome - Dörr, Helmuth-Günther; Madeja, Julia; Junghans, Claudia (Acta Paediatrica, 2015)
There is a scarcity of data on postnatal growth in children with CHARGE syndrome, a genetic disorder. This study analysed spontaneous growth and weight in German children with CHARGE from birth to the age of 6 years.This was a retrospective analysis of 19 children, nine females and 10 males, using data from child health records. Standard deviation scores (SDS) were calculated based on Swiss references.The median birthweight was 2950 g (-0.78 SDS), and the birth length was 49 cm (-0.5 SDS). There was a significant loss of median body length, at around 4 weeks of age from -0.5 to -2.3 SDS (p < 0.05). At 1 year, the median length was -2.6 SDS and it remained low until 5 years of age when the lowest value was found to be -2.8 SDS. There was a significant increase in median body mass index (BMI) from -1.15 SDS at 1 year to -0.15 SDS at 5 years (p < 0.01).Children with CHARGE syndrome displayed almost normal length and weight data at birth, with just one of the 19 infants having below average length for gestational age. However, postnatal growth was retarded during infancy and childhood, and the increase in BMI-SDS did not correlate with growth.
EVALuna2:18914